Development and application of magnesium alloy parts for automotive OEMs: A review - Liu, Bo; Yang, Jian; Zhang, Xiaoyu; Yang, Qin; Zhang, Jinsheng; Li, Xiaoqing (Journal of magnesium and alloys, 2023)
China is currently vigorously implementing the “energy conservation and emission reduction” and “dual carbon” strategies. As the most resource-advantaged light metal material in China, Magnesium (Mg) alloy is progressively expanding its application in automobile, rail transportation, aerospace, medical, and electronic products. Chongqing University, Shanghai Jiaotong University, and Australian National University have conducted extensive research on the preparation, properties, and processes of Mg alloys. In the past 20 years, the proportion of Mg alloy in the automotive industry has gradually expanded, whereas currently the design and development of Mg alloy parts for automobiles has rarely been reported. Thus, the application models and typical parts cases of Mg alloy are summarized mainly from the four systems of the whole vehicle (body system, chassis system, powertrain system, interior, and exterior system). Subsequently, two actual original equipment manufacturers (OEM) cases are used to introduce the development logic of reliable die-cast Mg alloy, including forward design, formability analysis, process design analysis, structural redesign, manufacturing, and testing, aiming to share the methods, processes, and focus of attention of automotive OEMs for developing Mg alloy parts to enhance the confidence and motivation of applying Mg alloy in automotive field. Eventually, the multiple challenges faced by Mg alloy materials are sorted out and how to face these challenges are discussed. National policies and regulations, environmental protection and energy saving, and consumer demand will continue to promote the application of Mg.